2017
DOI: 10.1016/j.carbon.2017.06.093
|View full text |Cite
|
Sign up to set email alerts
|

Modified facile synthesis for quantitatively fluorescent carbon dots

Abstract: A simple yet consequential modification was made to the popular carbonization processing of citric acid - polyethylenimine precursor mixtures to produce carbon dots (CDots). The modification was primarily on pushing the carbonization processing a little harder at a higher temperature, such as the hydrothermal processing condition of around 330 °C for 6 hours. The CDots thus produced are comparable in spectroscopic and other properties to those obtained in other more controlled syntheses including the deliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 41 publications
6
56
0
Order By: Relevance
“…As bioimaging probes, CDots are known to be biocompatible without any significant toxicity in vitro and in vivo ,,. Their optical performance is also high, with observed fluorescence quantum yields approaching unity in the spectral region overlapping that of green fluorescent protein (GFP) ,. The combination of high performance and non‐/low‐toxicity has stimulated broad interests in using CDots for cell and in vivo imaging applications ,,.…”
Section: Introductionmentioning
confidence: 99%
“…As bioimaging probes, CDots are known to be biocompatible without any significant toxicity in vitro and in vivo ,,. Their optical performance is also high, with observed fluorescence quantum yields approaching unity in the spectral region overlapping that of green fluorescent protein (GFP) ,. The combination of high performance and non‐/low‐toxicity has stimulated broad interests in using CDots for cell and in vivo imaging applications ,,.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported the preparation of CDs with excitation‐dependent and independent emission by controlling reaction temperature . Sun et al reported that the preparation of quantitatively fluorescent CDs is a promising approach for the improvement of optical properties and practical applications ,. However, the synthesis of CDs with both controllable excitation‐dependent or excitation‐independent emission and highly selective and sensitive PL properties continues to be a challenge for the present research field of CDs, preventing the development of these novel nanomaterials as well as investigation into the origin of these intriguing excitation dependent or independent PL properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the synthesis of CDs with both controllable excitation‐dependent or excitation‐independent emission and highly selective and sensitive PL properties continues to be a challenge for the present research field of CDs, preventing the development of these novel nanomaterials as well as investigation into the origin of these intriguing excitation dependent or independent PL properties. In the past decades, it has been documented that the chemical functionalization, reaction time, elemental content in CDs are key factors for controlling their optical properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a) The variation in optical bandgap with increasing concentration of fluorine in FBN estimated from plotting the Tauc plot using absorbance measurement that is fitted to an exponentially decaying curve. b) A plot comparing the various reported values for quantum yield of different 2D quantum dots with the FBN QDs having the highest value among them . c) The PL spectrum of FBN with the excitation shown in blue and emission in green.…”
mentioning
confidence: 99%